Система для проведения олимпиад по программированию - Еленский, С. В. (УАДО, 2002)
The system is intended for automatic hosting of programming contests. Users interact with the system through the site, the problems are published on. During the contest the contestants solve the problems on a personal computer. Then they send the solution of the problem to the system (solution is a program source code). The system automatically checks the solutions and reports the result to the contestants
Keywords: олимпиада по программированию; дистанционное обучение